Organizational Dynamics in Shared IT Leadership at Coal Mining Industry: A Case Study - Taufik, Asep Muhamad; Gunawan, Fandi; Setiyawan, Jodi; B.A.P, Basic Dirgantara; Shihab, Muhammad Rifki (JOIV : International Journal on Informatics Visualization, 2021)
The mining industry has faced intense challenges and disruptions from global trends. The mining industry needs to perform a transformation to survive. The important thing for mining companies in technological adoption is digital transformation. XYZ is a holding company with many subsidiaries with primary businesses in the coal mining sector spread throughout Indonesia. As part of digital transformation, one of the company's initiatives is to centralize IT resources into one organization, with the objective can share its utilization with all subsidiaries. IT's centralization and shared services caused problems, such as human resources in different company ownership, budget allocation among companies, and the structure of financing and utilization of IT resources for use. The problem was solved by mapping all the components' IT roles at the company based on the framework created by Applegate, Austin, and Soule. Mapping the role of IT in this company can be used as a guideline to make organizational change. Organizational changes that need to be done base on analysis is to change the structure of the organization of IT into a bimodal model, its combination between the Functional-Lean model and Matrix-Agile model. The Functional-Lean model provides organizations as a function to keep lean but can deliver high standard services and keep it stable. The Matrix-Agile model can provide agility for the organization to develop new and run projects. IT Governance at XYZ will use the Federal model.